How an urban parameterization affects a high‐resolution global climate simulation. (28th August 2020) - Katzfey, Jack; Schlünzen, Heinke; Hoffmann, Peter; Thatcher, Marcus
Abstract : The impact of urban areas on the global and regional climate has been assessed using the global Conformal Cubic Atmospheric Model (CCAM) including an urban canyon parameterization at a global resolution of 50 km. Simulations were produced with and without urban areas to assess urban impacts for the historical period 1980–2000. Two different land cover and urban datasets (one based on IGBP‐DIS, the other on MODIS) were tested. In addition, simulations were performed for the end of the 21st century with the RCP8.5 scenario. Evaluation of the historical climate simulations indicates realistic local urban effects, such as higher daily minimum air temperatures (tasmin), higher sensible heat flux and lower latent heat flux at urban grid cells. In regions with large fractions of urban areas, some regional changes are also noted. In addition, there are significant regional effects far away from the main urban areas, which are similar in magnitude to the effects of the different non‐urban land cover input datasets. Under the projected warming at the end of the 21st century (with no land cover change), there is a decrease in anthropogenic heating, primarily during wintertime. There is a slightly smaller increase in daily maximum temperature and a slightly larger increase in tasmin in urban areas compared to rural areas. This leads to a smaller increase in the diurnal temperature range within urban areas. The tasmin changes also imply an increase in the urban heat island effect for larger cities. The results of this sensitivity study show that there is a detectable impact of urban areas on high‐resolution global climate simulations. Consequently, there is a need to include urban areas in global simulations, as well as in studies of land‐use change. Abstract : Evaluation of the historical global climate simulations with and without an urban parameterization indicates the importance of including the urban parameterizations for realistic local urban effects, such as higher daily minimum air temperatures in urban areas as compared to rural areas. Some regional changes are also noted in regions with large fractions of urban areas, as shown in the figure. In addition, there are significant regional effects far away from the main urban areas, such as over Argentina.